2006
DOI: 10.1080/17450390600785079
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fumonisins on macrophage immune functions and gene expression of cytokines in broilers

Abstract: Fumonisin (FB 1 ), a mycotoxin, is produced by Fusarium moniliforme and F. proliferatum. A prevalence survey in Taiwan by our laboratory showed that there was a contamination rate of 40% in domestic animal feeds, and the average contaminated level was 4.5 mg/kg. Ninety-six birds were allotted into four treatments fed with diets containing 0 (control), 5, 10, or 15 mg/kg of FB 1 for three weeks. The results showed that the growth performance was not influenced by the FB 1 challenge, but relative bursa weight wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 19 publications
1
21
0
1
Order By: Relevance
“…Several reports in the literature have demonstrated the immunomodulatory properties of RJ. 16,17,21 Cheng et al 29 ) reported that RJ is effective against the hematopoietic dysfunction observed in X-irradiated mice and that is also promotes macrophage activity and hematopoietic stem cell proliferation. According to Sver et al 30 RJ stimulates antibody production and the proliferation of immunocompetent cells in mice and depresses humoral immune functions in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports in the literature have demonstrated the immunomodulatory properties of RJ. 16,17,21 Cheng et al 29 ) reported that RJ is effective against the hematopoietic dysfunction observed in X-irradiated mice and that is also promotes macrophage activity and hematopoietic stem cell proliferation. According to Sver et al 30 RJ stimulates antibody production and the proliferation of immunocompetent cells in mice and depresses humoral immune functions in rats.…”
Section: Discussionmentioning
confidence: 99%
“…FB 1 modulates immunity in animals, and it has immunocytotoxic effects by increasing IL-10 and IL-4 mRNA levels in the spleen of Balb/c mice together with the decrease in mRNA levels of IFN-γ and TNF-α compared with controls (Abbes et al 2015). Similarly, FB 1 could significantly inhibit the expression of IL-1β, IL-2, IFN-α and IFN-γ when broilers were exposed to 15 mg FB 1 per kg for 3 weeks (Cheng et al 2006). Together with AFB 1 or not, FB 1 increased levels of IL-4 and decreased levels of IL-10 in spleen mononuclear cells (SMC) in both in vivo and in vitro studies (Theumer et al 2002(Theumer et al , 2003.…”
mentioning
confidence: 84%
“…However, to date, there has been no generation of RNS reported in the study of FB 1 . When birds were fed diets containing FB 1 (5, 10 and 15 mg/kg) for 3 weeks, 15 mg FB 1 /kg feed had no effect on inducible nitric oxide synthase (iNOS) (Cheng et al 2006). …”
Section: Generation Of Reactive Oxygen Oxidative Stress and Reactivementioning
confidence: 99%
See 1 more Smart Citation
“…Concerning mycoplasma, we have preliminary evidence that mycoplasma suppresses interferon gene expression in chickens (unpublished observations). The fumonosin mycotoxins have been also reported to suppress ChIFN-α transcription (Cheng et al 2006).…”
Section: Discussionmentioning
confidence: 99%